PENERAPAN SENAM AEROBIK LOW IMPACT TERHADAP HEMODINAMIK, METABOLIK DAN ANTROPOMETRI PADA PASIEN OBESITAS - Berliana Ramadhona; Sanny Frisca; Novita Anggraini (Institut Kesehatan Pelamonia, 2026)
Obesity is defined as an accumulation of excess body fat, indicated by a Body Mass Index (BMI) of ≥30. It is caused by caloric intake exceeding energy expenditure, resulting in fat storage. Obesity serves as a precursor to various diseases. Management of obesity can be achieved through moderate-intensity physical activity specifically low-impact aerobic exercise as it increases energy expenditure and optimizes fat reserve burning without placing undue stress on the joints. To analyze nursing care involving low-impact aerobic exercise in terms of its effect on hemodynamic, metabolic, and anthropometric parameters in individuals with obesity. This scientific report employs an Evidence-Based Practice (EBP) design utilizing low-impact aerobic exercise. The intervention involved three respondents over six sessions (conducted in the morning and afternoon), with measurements of body weight, waist circumference, blood pressure, and random blood glucose taken before and after each exercise session. The results showed a decrease across all parameters. Systolic blood pressure decreased by 26 mmHg and diastolic pressure by 11 mmHg, while blood glucose levels dropped by 11–43 mg/dL per session. Additionally, body weight decreased by 0.06–0.30 kg, and waist circumference was reduced by 0.5–1 cm across all respondents. There were differences in hemodynamic, metabolic, and anthropometric values ​​before and after the daily low-impact aerobic exercise sessions.